2008
DOI: 10.1080/00926230802096358
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Emotional Predictors of Female Sexual Dysfunctions: Preliminary Findings

Abstract: The influence of cognitive and emotional variables on specific female sexual dysfunctions was investigated. A total of 207 women (160 without sexual problems and 47 with a Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) diagnosis of sexual dysfunction) answered a set of questionnaires assessing cognitive and emotional variables (cognitive schemas activated in sexual context - Questionnaire of Cognitive Schema Activation in Sexual Context (QCSASC); sexual beliefs - Sexual Dysfunctional Beliefs Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
52
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 23 publications
10
52
2
7
Order By: Relevance
“…Similar results have been found for men with sexual dysfunctions (Nobre & Pinto-Gouveia, 2006;Rowland, Georgoff, & Burnett, 2011). Studies conducted with clinical samples with different sexual problems have indicated that experiencing more negative emotions (negative affect) and less positive emotions (positive affect) during sexual activity was common in men and women with sexual desire problems (Carvalho & Nobre, 2010Geonét, de Sutter, & Zech, 2013;Mehta, Walls, Blood, & Shrier, 2014;Nobre, 2009;Nobre & Pinto-Gouveia, 2008; Running head: AFFECT, SEXUAL ORIENTATION AND SEXUAL PROBLEMS 5 Feldman, Black, Walls, Kensall, Lops, & Beardslee, 2012), men with erectile disorder (Nobre, 2010;Nobre & Pinto-Gouveia, 2000), women with symptoms of persistent genital arousal disorder (Carvalho, Veríssimo, & Nobre, 2013), and women with dyspareunia (Brauer, Ter Kuile, Laan, & Trimbos, 2009). …”
supporting
confidence: 65%
“…Similar results have been found for men with sexual dysfunctions (Nobre & Pinto-Gouveia, 2006;Rowland, Georgoff, & Burnett, 2011). Studies conducted with clinical samples with different sexual problems have indicated that experiencing more negative emotions (negative affect) and less positive emotions (positive affect) during sexual activity was common in men and women with sexual desire problems (Carvalho & Nobre, 2010Geonét, de Sutter, & Zech, 2013;Mehta, Walls, Blood, & Shrier, 2014;Nobre, 2009;Nobre & Pinto-Gouveia, 2008; Running head: AFFECT, SEXUAL ORIENTATION AND SEXUAL PROBLEMS 5 Feldman, Black, Walls, Kensall, Lops, & Beardslee, 2012), men with erectile disorder (Nobre, 2010;Nobre & Pinto-Gouveia, 2000), women with symptoms of persistent genital arousal disorder (Carvalho, Veríssimo, & Nobre, 2013), and women with dyspareunia (Brauer, Ter Kuile, Laan, & Trimbos, 2009). …”
supporting
confidence: 65%
“…It could be that conservative beliefs and beliefs about sex as a sin are specifically associated with some but not all sexual dysfunctions. Recent data seems to support this hypothesis, showing that these dimensions are significantly related to sexual desire disorders, but not to orgasm or pain disorders, while age-related beliefs seem to be associated with both desire and pain disorders (Nobre, 2003;Nobre & Pinto-Gouveia, 2004). In general, these results supported some etiological hypotheses about female sexual dysfunction presented in the clinical literature (Hawton, 1985;Heiman & LoPicollo, 1988;LoPiccolo & Friedman, 1988;Kaplan, 1979;Masters & Johnson, 1970).…”
Section: Discussionmentioning
confidence: 58%
“…18,24,25 Findings suggest the existence of specific cognitive schemas underlying sexual dysfunction and raise the question whether a more general cognitive organization could be proposed as a core vulnerability factor for sexual problems.…”
mentioning
confidence: 99%
“…20 A negative cycle could be established by the continuous interplay between negative thoughts and emotions, preventing the cognitive processing of erotic stimuli, and maintaining individual's poor sexual functioning. 18,24,25 Findings suggest the existence of specific cognitive schemas underlying sexual dysfunction and raise the question whether a more general cognitive organization could be proposed as a core vulnerability factor for sexual problems.…”
mentioning
confidence: 99%